Evaluating the efficacy of an educational ergonomics training module on improving positioning during the performance of venipuncture in phlebotomists - Maria Gjini; Tara L. Diesbourg (Human Factors in Healthcare)
Objective: To evaluate the efficacy of ergonomics training on altering phlebotomists' posture while performing venipuncture. Background: Phlebotomists often experience pain in their upper back, neck, and extremities due to holding non-neutral positions for prolonged periods. Ergonomics education has been found to increase workers’ postural awareness, which can improve working postures and reduce the risk for injury. While phlebotomists do receive some ergonomics training, it often focuses on lifting, which is less relevant to this population. Method: Participants were recorded performing venipuncture on a standardized patient. Participants then received an ergonomics training module and returned one week after completing the training to repeat the venipuncture process. Data were processed using Kinovea (v. 0.9.5) for angle digitizing and 3D-SSPP (VelocityEHS) for loading estimation. Results: Thoracic and hip flexion angles increased after completing the training module (95 % CI=10.782–4.312, p < 0.001 and 95 % CI=26.285–3.589, respectively), indicating that participants had adopted a more upright spine posture. L4/L5 compression and shear forces decreased after completing the training by an average of 336.55 N (p < 0.001) and 52.39 N (p < 0.001), respectively, indicating that participants’ disc loading significantly decreased after viewing the training module. Conclusion: These results suggest a promising ability for ergonomics training to reduce injury risk in this population during venipuncture. However, cumulative loading remains problematic, and more work needs to be done to reduce the remaining risk. Focusing on break schedules would be a valuable next step in protecting these workers. Application: These recommendations can be used in workplaces where workers develop awkward postures due to static work.